Mortgage Market Development, Savings, and Growth - Li, Xiaowei (IMF Working Papers; Working Paper ;, 2001)
Jappelli and Pagano (1994) argues that tightening the borrowing constraints in the mortgage markets promotes savings. Employing a six-period overlapping generations model with endogenous growth and a method of simulation calibrated on the Middle East, this paper demonstrates that the above argument is tenable only if consumers do not alter their tenure choices. Consumers do, however, postpone or forsake the purchase of a house under severely restrictive borrowing constraints, causing the savings and growth rates to fall. Therefore, for countries with scarce mortgage availability like those in the Middle East, expanding the mortgage markets to some extent is conducive to savings and growth.